PENERAPAN NILAI-NILAI MORAL PADA SANTRI TPQ AL-KHUMAIER PEKANBARU - Ida Windi Wahyuni (Generasi Emas: Jurnal Pendidikan Islam Anak Usia Dini, 2018)
Moral planting to children from an early age is very important considering that in the era of an increasingly global era, moral education as the basis of self-discipline to be an internal control tool in behaving consistently in religion. A child is naturally created in a state ready to receive good and evil. The habituation of religious and moral values ​​for early childhood is very important to apply as early as possible to the most basic foundation in the process of growth and development of children. The objectives of this research are (1) To describe TPQ Al-Khumaier program, (2) To describe the application of moral values ​​to students by TPQ Al-Khumaier teacher (3) To know the obstacles in applying moral values ​​to the students of TPQ Al-Khumaier and looking for a solution. The results of this study indicate that the program TPQ Al-Khumaier has been implemented according to the program prepared by the school in collaboration with Kemenag Pekanbaru. The application of santri moral values ​​has been practiced in the activities and the process of habituation and modeling of the teachers. The obstacles are the duration of the meeting, social outside TPQ, including social media at home and in the neighborhood where students live.